Microwave Flow Chemistry as a Methodology in Organic Syntheses, Enzymatic Reactions, and Nanoparticle Syntheses. Issue 1 (2nd October 2018) - Horikoshi, Satoshi; Serpone, Nick
Abstract: Several studies have used microwaves as a heat source for carrying out various types of reactions employing circulation reaction vessels. The microwave flow chemical synthesis methodology is most appropriate in the use of microwaves in chemical syntheses. It can attenuate the problem of microwave heating (non‐uniform heating and penetration depth) and maximize the benefits (rapid heating and first temperature adjustments). In this brief review, we examine and explain some of the relevant features of microwave heating with applicative examples of the usage of microwave flow chemistry equipment in carrying out organic syntheses, enzymatic reactions, and (not least) nanoparticle syntheses. Abstract :